2007
DOI: 10.1001/archderm.143.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Second Lymphomas and Other Malignant Neoplasms in Patients With Mycosis Fungoides and Sézary Syndrome

Abstract: Setting: Nine population-based US cancer registries that constitute the Surveillance, Epidemiology, and End Results Program (SEER-9), and Stanford University referral center cohort of patients with cutaneous lymphoma.Patients: Patients with mycosis fungoides or Sézary syndrome from the SEER-9 registry diagnosed and followed up from 1984 through 2001 and from the Stanford University cohort diagnosed and followed up from 1973 through 2001.Main Outcome Measures: Relative risk was estimated using the standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 33 publications
4
80
1
4
Order By: Relevance
“…Visceral abnormalities seen radiologically in MF could be secondary to either another unrelated cancer (second malignancies are not uncommon in MF/SS [86][87][88] or to an infectious disorder and not to MF/SS.…”
Section: Revision To M Classificationmentioning
confidence: 99%
“…Visceral abnormalities seen radiologically in MF could be secondary to either another unrelated cancer (second malignancies are not uncommon in MF/SS [86][87][88] or to an infectious disorder and not to MF/SS.…”
Section: Revision To M Classificationmentioning
confidence: 99%
“…Our findings are complementary to those of others who have shown that patients with MF/SS are at increased risk for developing a second primary lymphoma, particularly classic Hodgkin lymphoma. 34 It is uncertain why patients with MF/SS are at increased risk of developing a second primary lymphoma. In any event, recognition of the association of MF/SS and development of other lymphomas is essential when evaluating FNAB specimens, especially when allocating the limited sample obtained by FNAB for various ancillary studies such as flow cytometry, immunohistochemistry, and molecular studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced disease may develop visceral dissemination, and the most commonly involved organs are the lungs, spleen, liver, gastrointestinal tract, kidneys, thyroid gland, pancreas, bone marrow, and heart [16,29]. MF has also been described in the head and neck in advanced stages with reports of spread to the larynx, oral cavity, oropharynx, hypopharynx, cervical esophagus, paranasal sinuses, and the aerodigestive tract [3,8,15,16,22]. If peripheral blood involvement is present, patients are considered to have Sezary syndrome (SS) [29].…”
Section: Introductionmentioning
confidence: 99%